Non-hip, non-spine fractures drive healthcare utilization following a fracture: the Global Longitudinal Study of Osteoporosis in Women (GLOW). - Ioannidis, G; Flahive, J; Pickard, L; Papaioannou, A; Chapurlat, R; Saag, K; Silverman, S; Anderson, F; Gehlbach, S; Hooven, F; Boonen, S; Compston, J; et al. (2013)
UNLABELLED: We evaluated healthcare utilization associated with treating fracture types in >51,000 women aged ≥55 years. Over the course of 1 year, there were five times more non-hip, non-spine fractures than hip or spine fractures, resulting in twice as many days of hospitalization and rehabilitation/nursing home care for non-hip, non-spine fractures. INTRODUCTION: The purpose of this study is to evaluate medical healthcare utilization associated with treating several types of fractures in women ≥55 years from various geographic regions. METHODS: Information from the Global Longitudinal Study of Osteoporosis in Women (GLOW) was collected via self-administered patient questionnaires at baseline and year 1 (n = 51,491). Self-reported clinically recognized low-trauma fractures at year 1 were classified as incident spine, hip, wrist/hand, arm/shoulder, pelvis, rib, leg, and other fractures. Healthcare utilization data were self-reported and included whether the fracture was treated at a doctor's office/clinic or at a hospital. Patients were asked if they had undergone surgery or been treated at a rehabilitation center or nursing home. RESULTS: During 1-year follow-up, there were 195 spine, 134 hip, and 1,654 non-hip, non-spine fractures. Clinical vertebral fractures resulted in 617 days of hospitalization and 512 days of rehabilitation/nursing home care; hip fractures accounted for 1,306 days of hospitalization and 1,650 days of rehabilitation/nursing home care. Non-hip, non-spine fractures resulted in 3,805 days in hospital and 5,186 days of rehabilitation/nursing home care. CONCLUSIONS: While hip and vertebral fractures are well recognized for their associated increase in health resource utilization, non-hip, non-spine fractures, by virtue of their 5-fold greater number, require significantly more healthcare resources.